Начальное деформирование упругого полупространства при кинематическом воздействии - Янютин, Е. Г.; Богдан, Д. И.; Толбатов, Евгений Юрьевич (НТУ "ХПИ", 2013)
The elastic oscillations of a half-space in case of the kinematical influence set on its surface are described in the article. Nonaxisymmetric statement of the second boundary value problem is considered. The problem is solved by using of expansion in Fourier series. The numerical example on finding of movings on depth of the half-space is considered at the known kinematical impact on it's surface.
Keywords: система неосесимметричная; уравнения интегральные; теория упругости; уравнения Ляме